Factors associated with risk and prognosis of intensive care unit admission in patients with acute leukemia: a Danish nationwide cohort study. Issue 10 (24th August 2022) - Maeng, Cecilie Velsoe; Christiansen, Christian Fynbo; Liu, Kathleen Dori; Kamper, Peter; Christensen, Steffen; Medeiros, Bruno C.; Østgård, Lene Sofie Granfeldt
Abstract: Identifying risk factors for intensive care unit (ICU) admission in acute leukemia (AL) patients may guide decision-making and improve prognosis. We included all adult AL patients receiving high-intensive chemotherapy in Denmark from 2005 to 2016. We examined risk factors [crude and adjusted (a) relative risks (RRs) with 95% confidence intervals (CI)] and calculated RRs of death after 1-, 3-, and 5-years in ICU-admitted patients compared with matched cohorts. In 1417 AML and 306 ALL patients, the 1-year risk of ICU admission was 28.1% for AML and 26.4% for ALL patients, with the majority related to the first course of chemotherapy. Performance status >1 was associated with increased risk. The 1-year mortality was higher in ICU-admitted patients (AML: 69.7 vs. 35.0% [aRR 2.74;CI = 2.17–3.47]; ALL 65.0 vs. 20.0% [aRR 3.04;CI = 1.54–6.02]). The excess mortality decreased with time. In this study, performance status was associated with increased risk of ICU admission and identifies high-risk patients. ICU admission was associated with high mortality, especially within the first year.